APPLICATION OF MANAGEMENT AUDIT TO THE MARKETING FUNCTION AT PT. (PERSERO) CIPTA NIAGA BRANCH MANADO - Diana Nova Lintong (ACCOUNTABILITY, 2023)
This study aims to determine the application of management audits to the company's marketing function. The data used in this research includes primary and secondary data, while the data collection method is carried out through field research and literature. To assess the effectiveness of the marketing function, analysis is used by comparing the marketing function according to the theory and practice applied by the company. The results of this study are conveyed regarding the analytical methods that must be carried out in the inspection, the work program that must be made by the examiner, the problems found in the examination, and the necessary recommendations for the preliminary survey, review, and testing of the management control system. Detailed testing and report development while the work program must be made involves evaluating the company's marketing activities and marketing function issues and formulating recommendations. The problems found and suggestions are that management needs to implement a practical marketing philosophy, marketing information used by management needs to be more adequate, marketing plans need to be strategically oriented, and marketing activities carried out by administration must reflect operational efficiency